Diseño de dispositivo XYZ para celda caliente. - Alonso, Marcelo G. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2015)
Fil. Alonso, Marcelo G.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina